Novel Family of Gynecologic Cancer Antigens Detected by Anti-HIV Antibody - Ewa M. Rakowicz-Szulczynska; David G. McIntosh; Peter Morris; McClure Smith (Hindawi Limited, 1994)
Objective: The reactivity of gynecologic cancer proteins with monoclonal antibody (MAb) directed against the human immunodeficiency virus I (HIV-I) was tested.